Experimental evaluation of an environmentally friendly drilling fluid for clay stabilization in shale formations - Ali Momeni; Seyyed Alireza Tabatabaei-Nezhad; Seyyed Shahab Tabatabaee Moradi (Scientific Reports)
Abstract To face the problems of shale drilling, oil-based fluids, mineral salts, and polymers are used, but they have limitations such as high preparation cost, hazardous environmental impact, and limited applicability in high-pressure, high-temperature environments. Therefore, introducing an environmentally friendly drilling fluid capable of inhibiting clay swelling can be beneficial for drilling shale layers and other layers containing swelling clays. Glycerin is ecologically friendly and has high stability under various environmental conditions. In the present research, a thorough set of experimental tests, including a bentonite sedimentation test, free swelling test, bentonite inhibition test, cuttings dispersion test, and visual observation of swelling, have been conducted. In all experiments, bentonite and shale cuttings were utilized as representative clay samples, with their mineralogy precisely characterized using advanced techniques such as zeta potential analysis, X-ray diffraction, and particle size distribution analysis. The representative clay samples were then brought into contact with different compositions of drilling fluids, including glycerin-based fluids and an index showing the inhibition characteristics of the fluids was reported for each test. The results indicate that glycerin-based fluids at concentrations of 100%, 90%, and 80% exhibit a significantly high capability to control clay swelling, outperforming conventional KCl-based fluids in all tests. While the 70% glycerin-based fluid showed superior performance in most tests, its results in bentonite sedimentation and cutting recovery were comparable to those of KCl-based fluids. Additionally, cutting recovery tests revealed that glycerin-based fluids not only outperform KCl-based fluids but also maintain their effectiveness more consistently with increasing temperature, highlighting their potential as a reliable and temperature-stable alternative for inhibiting clay swelling in drilling operations.